Gene expression differences for drought stress response in three cool‐season turfgrasses. Issue 1 (24th February 2021) - Bushman, B. Shaun; Robbins, Matthew D.; Warnke, Scott E.; Martin, Ruth; Harris‐Shultz, Karen; Amundsen, Keenan E.
Abstract: Many efforts in the USA have focused on turfgrass tolerances to drought imposition as means to reduce their need for irrigation. As part of this effort, our research groups have subjected multiple species and varieties to drought and collected transcript expression profiles of genes that were differentially expressed under stress and control conditions. We generated lists of transcripts and gene families differentially expressed in Kentucky bluegrass, perennial ryegrass, and creeping bentgrass; and we compared each species' differentially expressed transcript set across all three species. The gene families with differentially expressed transcript isoforms in each species and across all three species were annotated and characterized. By examining these datasets, we found key genetic mechanisms by which these species respond to drought stress. Specific genes, such as ABA responsive LEA homologs, show their crucial nature upon drought stress in all three species. Other gene families, such as E3 ubiquitin ligases, exhibited different gene family members in each species and highlight the species‐specific responses to drought.